INTEGRATION OF ISLAMIC EDUCATION AND CBE FOR ECONOMIC AND SOCIAL DEVELOPMENT OF THE COMMUNITY AT HIDAYATULLAH ISLAMIC BOARDING SCHOOL IN BONTANG CITY - Muhsin, Muhsin; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Integration of Islamic education with Community-Based Education (CBE) offers a strategic solution in improving the economic and social development of the community. This study explores this approach in Pesantren Hidayatullah Bontang City, focusing on the synergy of religious education and community involvement to create socio-economic impacts. This study uses a descriptive qualitative method, observing the success of the integration model in supporting pesantren-based economic empowerment. The results show that this approach is able to increase community participation, management of the pesantren economy, and strengthening social solidarity.